Sumpah Pocong Dalam Penyelesaian Sengketa di Polagan Sampang Madura - Choirunnisa’, Chaja (Al-Jinayah: Jurnal Hukum Pidana Islam, 2018)
Abstract: This article discusses about pocong oath of the dispute resolution in Madegan Polagan Sampang Madura. Pocong oath is carried out as a middle way since there is not enough evidence and witness to be processed through a court. Pocong oath is carried out by a statement submitted to the village head of Polagan. The statement must also be known by the police chief and the local military command. An overview of Islamic law regarding pocong oath in the case of land dispute resolution in Polagan Village of Sampang Madura is included in the decisoir oath. In the case of no evidence at all, the judge will give a decisoir oath or a breaker oath to solve the case completely. By using a decisoir oath tool, the judge's decision will depend solely on the sound of the oath and the courage of the oath-swearman. Based on this practice, pocong oath in Islamic law is permitted because the oath strengthens proof. Keywords: Pocong oath, land dispute, Islamic law. Abstrak: Artikel ini membahas tentang sumpah pocong terhadap penyelesaian sengketa di Madegan Polagan Sampang Madura. Sumpah pocong dilakukan sebagai jalan tengah karena tidak adanya cukup bukti dan saksi jika diproses melalui pengadilan. Sumpah pocong dilaksanakan dengan membuat surat pernyataan yang diajukan kepada kepala desa Polagan. Surat pernyataan tersebut juga harus diketahui oleh Kapolsek dan Danramil setempat. Tinjauan hukum Islam tentang sumpah pocong dalam kasus penyelesaian sengketa tanah di Desa Polagan Sampang Madura adalah termasuk dalam sumpah decisoir. Berdasarkan praktik tersebut maka sumpah pocong dalam hukum Islam diperbolehkan karena sumpah tersebut menguatkan pembuktian. Kata kunci: Sumpah pocong, sengketa tanah, hukum Islam.